The role of the court in invoking danger in criminal proceedings - كاظم, رشا علي; الشمري, كاظم عبد الله (Journal of Legal Sciences, 2021)
The study of criminal danger is a part of a common phenomenon in criminal studies, namely, the conflict between traditional legal concepts and the new requirements of modern criminal policy, and the primacy of development and response to the requirements of modern human life. Criminal law scholars have recognized the importance of danger, especially after they have determined that the danger of crime is not limited to material damage, but rather to aggression against fundamental interests of the group, which is the possibility of damage. In particular, development and progress have led to the emergence of new areas in which the danger is the basis of the criminalization of related acts such as security, economy, trade, modern industries, transport, communications and the environment, in addition to the development in the fields of practicing some professions such as medicine, construction, engineering and others. Legislative systems differed in how to deal with this issue. The question was whether the court's authority to assess dangerous behavior and the appropriate sentence was left to be regulated or regulated according to legal rules and criteria to be determined.                                                       This research aims to focus on establishing a precise and disciplined rule of how to invoke danger in judicial decisions as an element in the conduct of the crime and the duty to confirm and memorize it, in addition to the extent to which the Federal Court of Cassation controls the judgments and decisions of the court of the subject.